2019
DOI: 10.5114/pg.2019.90093
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar biological drugs in the treatment of inflammatory bowel diseases

Abstract: Within the last 20 years, tumour necrosis factor inhibitors have been proven to be effective in achieving and maintaining clinical and endoscopic remission in patients with Crohn's disease and ulcerative colitis. Since 2013, when infliximab originator lost its patent protection, patients with inflammatory bowel diseases (IBDs) in Poland have also been treated with biosimilar drugs. Biosimilars are drugs with high similarity to their reference products in terms of physicochemical properties, including structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…As in inflammatory arthritis, TNF-inhibitors have drastically changed the prognosis of inflammatory bowel diseases (IBDs), and BIOs have also become a reality in this peculiar category of patients. The only studies regarding the use of BIOs in paediatric age are focussed on IBDs and evaluated the efficacy, safety and immunogenicity of infliximab [32][33][34][35][36]47]. Alongside our data, they showed that switching from the reference drug to the BIO did not affect the efficacy of the drug and did not increase the rate of ADEs in a real-world setting [32][33][34][35][36]50].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As in inflammatory arthritis, TNF-inhibitors have drastically changed the prognosis of inflammatory bowel diseases (IBDs), and BIOs have also become a reality in this peculiar category of patients. The only studies regarding the use of BIOs in paediatric age are focussed on IBDs and evaluated the efficacy, safety and immunogenicity of infliximab [32][33][34][35][36]47]. Alongside our data, they showed that switching from the reference drug to the BIO did not affect the efficacy of the drug and did not increase the rate of ADEs in a real-world setting [32][33][34][35][36]50].…”
Section: Discussionsupporting
confidence: 52%
“…The only studies regarding the use of BIOs in paediatric age are focussed on IBDs and evaluated the efficacy, safety and immunogenicity of infliximab [32][33][34][35][36]47]. Alongside our data, they showed that switching from the reference drug to the BIO did not affect the efficacy of the drug and did not increase the rate of ADEs in a real-world setting [32][33][34][35][36]50]. Even though we did not directly evaluate the efficacy and safety of infliximab in our study, and IBDs and JIA are different diseases, these results are consistent, supporting that biosimilars also show comparable properties to originators in paediatric age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Caco-2 cell line (colon adenocarcinoma cell line) cultured under certain conditions may resemble enterocytes present in a normal intestine and previously have been used as a model system in research (1). The intestinal epithelium has the ability to function as a barrier between the external and internal environment.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal epithelium has the ability to function as a barrier between the external and internal environment. This ability is essential for human health, and disorders in this functioning due to increased intestinal permeability are associated with diseases such as: inflammatory bowel disease (IBD), irritable bowel syndrome (IBS) or celiac disease (1). There are reports that tofacitinib may improve the functioning of the cellular barrier in the form of the intestinal epithelium in patients with enteritis (2).…”
Section: Introductionmentioning
confidence: 99%